PENERAPAN STANDAR PELAYANAN DI BAJAMBA RESTORAN PREMIER BASKO HOTEL PADANG - Maharani, Miranda; Chair, Ira Meirina; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aims to determine the application of the standard of service in Bajamba Premier Basko Hotel Restaurants Padang terms of 16 indicators that greeting the guest, escorting and sitting the guest, unfolding guest napkin, pouring ice water, presenting the menu,taking order, serving bread and butter, adjustment, serving the food, clear_up, crumbing down, presenting tea or coffee, presenting the bill, bid farewell, and table setting. The research is a qualitative descriptive survey method. Objects in this study degustation which amounted to 7 waiter. Data collection techniques by using the method of observation, interviews, and documentation.The results of this study indicate that the stages unfolding guest napkin, pouring ice water, serving bread and butter, serving the food, clear_up, crumbing down, serving the dessert, presenting the bill, and table setting . of seven waitresses have all been in the service of food and beverages in accordance with service standards that have been set by management in Bajamba Premier Basko Hotel Restaurants Padang. on stage greeting the guest, escorting and sitting the guest, presenting the menu, taking order, adjustment, presenting tea or coffee, and bid farewell of seven waiters who do not all stages of service standards in accordance with service standards that have been set by management in Bajamba Premier Basko Hotel Restaurants Padang.Keywords: Standard Service, Bajamba Restaurants